2008
DOI: 10.1116/1.2981067
|View full text |Cite
|
Sign up to set email alerts
|

Properties of octadecanethiol self-assembled monolayers deposited on GaAs from liquid and vapor phases

Abstract: Octadecanethiol (ODT), CH3(CH2)17SH, self-assembled monolayers (SAMs) were deposited on GaAs (100) substrates from solution and from vapor phase. The monolayers assembled from solution were prepared by incubating the substrate in a dilute millimolar ODT/ethanol solution, while vapor-deposited monolayers were prepared from vapor phase transport of ODT in an ultrahigh vacuum environment. The structural and optical characteristics of the resulting SAMs were examined with contact angle (CA) analysis, photoluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…41,53,54 In this paper, we study the use of SAMs of 1-octadecanethiol (ODT, CH 3 [CH 2 ] 17 SH) to passivate and protect n-type GaAs (100) surfaces. Long-chain ODT was chosen since previous studies have shown that the passivation of III−V surfaces improves with increasing alkyl chain length 55,56 due to denser and better ordered SAMs. 57 Using synchrotron-radiation photoemission spectroscopy (SRPES), we demonstrate that an optimized chemistry can lead to GaAs−SAM interfaces that are free of Ga and As oxides and do not show any band bending, even after air exposure.…”
Section: Introductionmentioning
confidence: 99%
“…41,53,54 In this paper, we study the use of SAMs of 1-octadecanethiol (ODT, CH 3 [CH 2 ] 17 SH) to passivate and protect n-type GaAs (100) surfaces. Long-chain ODT was chosen since previous studies have shown that the passivation of III−V surfaces improves with increasing alkyl chain length 55,56 due to denser and better ordered SAMs. 57 Using synchrotron-radiation photoemission spectroscopy (SRPES), we demonstrate that an optimized chemistry can lead to GaAs−SAM interfaces that are free of Ga and As oxides and do not show any band bending, even after air exposure.…”
Section: Introductionmentioning
confidence: 99%
“…H. A. Budz et al reported that SAMs of octadecanethiol deposited on GaAs from liquid and vapor phases can inhibit the oxidation of the surface for an extended period of time [10,11]. In addition, H. A. Budz [11] and Shen Ye et al [12] reported that SAMs of alkanethiol constructed on GaAs had a hydrophobic property.…”
Section: Introductionmentioning
confidence: 99%
“…ODT SAMs provide a reactive sulfur head (SH) at the end of the 18-carbon long chain. Although thiol SAMs are mostly studied on Au surfaces, some studies on III-V materials have also been reported [14][15][16][17][18][19][20][21]. Majority of the work on thiol SAMs on III-V compounds investigate GaAs [14][15][16][17] but there are a few examples on InP [18], GaP [19] and InAs [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Although thiol SAMs are mostly studied on Au surfaces, some studies on III-V materials have also been reported [14][15][16][17][18][19][20][21]. Majority of the work on thiol SAMs on III-V compounds investigate GaAs [14][15][16][17] but there are a few examples on InP [18], GaP [19] and InAs [20,21]. Typically, the active sulfur end of the thiol creates sulfur bonds on the surface, protecting the surface from oxidation while satisfying dangling bonds.…”
Section: Introductionmentioning
confidence: 99%